Catatan Kelompok Ascomycota Makroskopik di Indonesia - Ivan Permana Putra (Pro-Life, 2021)
Ascomycota is the largest Phylum in the Kingdom of Fungi. Most of the members of this group are microscopic, but fews are also produce macroscopic ascomata. Due to their large size and visible without the aid of a microscope, this group is often confused as Basidiomycota. This paper is a literature-based quantitative research. To date, 11 macroscopic Ascomycota from Indonesia have been reported, namely: Elaphomyces tropicalis sp. nov., Chlorociboria cf. aeruginosa, Podostroma cf. cornu-damae, Onygena sp., Morchella aff. deliciosa, Morchella sp., Scutellinia sp., Trichaleurina javanica, Cookeina speciosa, Cookeina tricholoma, Phillipsia sp., Daldinia spp., and Xylaria spp. The macrofungi are classified into 5 orders and 9 Families. Exploration and inventory efforts are need to be done more actively to increase the information on the diversity of masroscopic Ascomycota in Indonesia.